An Efficient and Recycling Catalyst for the One-Pot Three-Component Synthesis of Substituted 3,4-Dihydropyrimidin-2(1H)-ones - Taoues Boumoud; Boudjemaa Boumoud; Salah Rhouati; Ali Belfaitah; Abdelmadjid Debache; Paul Mosset (E-Journal of Chemistry)
The Biginelli one-pot three-component cyclocondensation was applied in this work to prepare 3,4-dihydropyrimidinone and its analogues using the first derivative of lead, Pb(NO3)2, as a recycling catalyst, from a diversity of aromatic aldehydes, β-ketoesters and urea. The reaction was carried out in refluxing acetonitrile and afforded the target molecules in good to excellent yields. The method offers several advantages including high yields of the products, short reaction times and easy experimental workup procedure